Pengaruh pH Terhadap Pembentukan Senyawa Kompleks Kobal(II)Hipoksantin - Devina Ingrid Anggraini; Suhartana suhartana; pardoyo pardoyo (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2011)
Cobalt ion has electron configuration that enable as a center ion of complex compound such as cobalt(II)hypoxanthine. Complexation of cobalt(II)hypoxanthine is necessary to learnad due to its biological system involvement in purine catabolism. Complex formation is affected by pH on cobalt(II)hypoxanthine complex formation. This effect was studied by varying solution pH From 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, and complex formed was extracted using chloroform.qualitative characterization of the complex was performed by analysing its infrared and ultraviolet spectra, and quantitative test using atomic absorption spectrophotometer. Result show that optimum process was reached at pH of 9. Cobalt bonds with hypoxanthine via N9, as supported by its ultraviolet and infrared spectra as well.